2019
DOI: 10.1080/1828051x.2018.1548915
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of raw and fried big-scale sand smelt (Atherina boyeri) from trasimeno lake

Abstract: The aim of this research was to investigate the nutritional composition of raw and fried bigscale sand smelt (Atherina boyeri) from Trasimeno Lake. Four hundred big-scale sand smelts were caught with nets and analysed immediately. We created a total of 20 batches with 20 whole fish in each batch. Ten batches were analysed as raw samples, while the other 10 batches were analysed after being fried in sunflower oil at a temperature of 190 C for 3 min (deep fat frying). The pH, proximate composition, fatty acid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 34 publications
4
6
4
Order By: Relevance
“…The highest lipid content of sand smelt was observed in summer as 2.86%, with significant variation amongst seasons (p<0.05) (Table 1). The lipid contents of sand smelt in the current study were similar to the results of previous studies (Dal Bosco et al 2019;Prato and Biandolino 2012). Moreover, Bouriga et al (2014) also found that the fat content of the sand smelt (Atherina lagunae ) populations from Kerkennah Islands and Bizerta Lagoon were maximal at the end of springbeginning of summer and minimal at the end of the winter.…”
Section: Proximate Compositionsupporting
confidence: 91%
See 4 more Smart Citations
“…The highest lipid content of sand smelt was observed in summer as 2.86%, with significant variation amongst seasons (p<0.05) (Table 1). The lipid contents of sand smelt in the current study were similar to the results of previous studies (Dal Bosco et al 2019;Prato and Biandolino 2012). Moreover, Bouriga et al (2014) also found that the fat content of the sand smelt (Atherina lagunae ) populations from Kerkennah Islands and Bizerta Lagoon were maximal at the end of springbeginning of summer and minimal at the end of the winter.…”
Section: Proximate Compositionsupporting
confidence: 91%
“…It was found that the contents of stearic acid of sand smelt changed considerably during the seasons (p<0.05) while no statistical differences were found for palmitic acid. Many authors have reported myristic, palmitic and stearic acid as major acids among SFAs for the same and other fish (Dal Bosco et al, 2019;Rahman et al, 1995;Tanakol et al, 1999;Yavuzer, 2020). Although, Dal Bosco et al (2019) reported similar results value for stearic acid, Tanakol et al (1999) and Yavuzer (2020) found higher results values of the amounts of palmitic acid and stearic acid in sand smelt from the Marmara Sea (27.1 -7.0%) and Hirfanlı Dam, Turkey (26.85-6.40%), respectively.…”
Section: Saturated Fatty Acids (Sfa)mentioning
confidence: 82%
See 3 more Smart Citations